Europe and the people without market history - Fargher-Navarro, Lane F. (Frontiers in Human Dynamics, 2025)
Wolf’s Europe and the People Without History has significantly influenced anthropology and social science, marking a crucial point in the discipline’s engagement with historical perspectives. However, the conceptual frame employed by Wolf excluded an important aspect of human life from consideration among native peoples of North America – market exchange. My goal in this essay is to reexamine the role of market exchange in Native North America. But rather than rehash the critiques of the substantivist-Marxist-Polanyian frame, I propose the use of an alternative approach drawn from the New Institutional Economics. My goal is to explore the diverse ways in which social institutions (or rules) governed the social construction of private goods, especially the creative ways humans generate institutions to facilitate exchange in the absence of reciprocity, which builds trust by embedded exchange in social relationships. I present ethnohistoric and archeological data from Alaska (Iñupiaq), Arizona (Hohokam), and Illinois (Cahokia) to demonstrate that native peoples engaged in commodity exchange, including market exchange, prior to European contact. Evidence includes detached specialization, patterned diversity/distributional approach (an archeological marker of market exchange), and strategies used to build trust and overcome cooperation problems generated by anti-market behaviors.